Effects of the Maritime Silk Road on Port Development along the Route of Belt and Road Initiative - Mehmet Serdar Çelik; Demir Ali Akyar; Bulut Ozan Ceylan (Journal of Transportation and Logistics)
The Belt and Road Initiative (BRI) is a comprehensive strategy devised by the Chinese government to promote global connectivity through multiple pathways. The Silk Road Economic Belt (SREB) is primarily concerned with establishing land-based links that stretch across continents. In contrast, the Maritime Silk Road (MSR) is focussed on creating sea-based corridors that connect different maritime hubs. The ports situated along the MSR are not only infrastructural institutions; rather, they play a crucial role in facilitating commerce, fostering economic development, shaping geopolitical strategies, and facilitating cultural interchange. The objective of this research is to not only delineate the existing nodes and ports comprising the MSR but also ascertain prospective sites that might be smoothly included into this maritime infrastructure. A comprehensive comprehension of MSR necessitates an evaluation of the perspectives held by various international stakeholders. The basis of this study is a comprehensive literature analysis that aimed to analyse the development of ports inside the MSR framework since its establishment in 2013. Despite the significance of the programme, there is a notable scarcity of comprehensive studies that expressly examine port involvement in MSR. The existence of this gap serves to highlight the originality and uniqueness of our study. Through an analysis of port ownership patterns, recent investment flows, current political climates, and the extent of MSR’s involvement, this report provides a detailed perspective on the marine aspect of China’s overarching goal.